Social Capital and Housing Affordability: Evidence from China. Issue 8 (2nd August 2016) - Yi, Daichun; Huang, Yuhong; Fan, Gang-Zhi
ABSTRACT: This article attempts to examine the problem of housing affordability in China based on a set of household-level survey data. In contrast to the previous studies, our study focuses on the important implication of social capital for households' house-purchasing decisions in this country. Our results show that household expenditures on the relations with parents and other relatives are important determinants for homeownership in China. We also find evidence that house-purchasing decisions are significantly affected by relatives-related variables such as number of immediate relatives in the same city, distance from parents, educational years of family head's father, and whether parents are alive. Our research helps shed new light on the high homeownership rates in urban China.